Intellectual virtue signalling - Levy, NL (University of Illinois Press, 2023)
Discussions of virtue signaling to date have focused exclusively on the signaling of the moral virtues. This article focuses on intellectual virtue signaling: the status-seeking advertising of supposed intellectual virtues. Intellectual virtue signaling takes distinctive forms. It is also far more likely to be harmful than moral virtue signaling, because it distracts attention from genuine expertise and gives contrarian opinions an undue prominence in public debate. The article provides a heuristic by which to identify possible instances of intellectual virtue signaling. When people with no relevant expertise rapidly move to offer their opinions on a wide range of topics as soon as these topics become fashionable or newsworthy, and especially when these opinions are contrarian, we should suspect them of intellectual virtue signaling.